COPING STRATEGY OF PLWHA THROUGH ECONOMIC EMPOWERMENT: A LITERATURE REVIEW - Hannin Pradita N Soulthoni; Johanna Debora Imelda (Social Welfare Study Program, 2021)
Abstract. In Indonesia, the HIV-AIDS case is one of the sensitive issues in which the spread of this case continues to increase every year. The problems of people living with HIV-AIDS (PLWHA) consist of physical dimensions, economic dimensions, and social dimensions. A potential intervention model that can be done to help break the vicious circle for PLWHA sufferers is economic empowerment. So it is necessary to support microeconomic finance in carrying out conventional financial practices which can later have implications for health and economic success for PLWHA through collaboration. PLWHA faces conditions of disadvantage in the form of stigma, physical decline, and economic problems. For this reason, it is necessary to have an appropriate coping strategy from PLWHA in the form of empowering micro-business economies. The implementation of economic empowerment needs to require a good support system in the form of collaboration in which the family, government, and NGOs help carry out economic empowerment. The research method used is a literature review. The journal criteria that have been selected by researchers in this study discuss PLWHA, the existence of similarities in research in the form of coping strategies for economic empowerment, as well as being relevant and accredited. The results of the analysis identified PLWHA in overcoming the economic problems they face can be assisted through a coping strategy that focuses on problems (problem-focused coping) by involving collaborators in overcoming these problems through economic empowerment.Abstrak. Di Indonesia kasus HIV-AIDS merupakan salah satu isu sensitif di mana dalam penyebarannya kasus ini terus mengalami peningkatan setiap tahun. Permasalahan orang dengan HIV-AIDS (ODHA) terdiri dari dimensi fisik, dimensi ekonomi, dan dimensi sosial. Model intervensi potensial yang dapat dilakukan dalam membantu melepaskan lingkaran setan bagi penderita ODHA adalah dengan pemberdayaan ekonomi. Sehingga perlu dukungan keuangan mikro ekonomi dalam menjalankan praktik keuangan konvensional yang nantinya dapat menghasilkan implikasi dalam keberhasilan kesehatan dan perekonomian bagi ODHA dengan cara kolaborasi. ODHA menghadapi kondisi tidak beruntung dalam bentuk stigma, penurunan fisik, dan masalah ekonomi. Untuk itu perlu adanya coping strategi yang tepat dari ODHA dalam bentuk pemberdayaan ekonomi usaha mikro. Pelaksanaan pemberdayaan ekonomi perlu membutuhkan support system yang baik dalam bentuk kolaborasi di mana swasta, pemerintah, serta LSM membantu menjalankan pemberdayaan ekonomi tersebut. Metode penelitian yang digunakan adalah literature review. Kriteria jurnal yang telah dipilih oleh peneliti dalam penelitian ini membahas mengenai ODHA, adanya kesamaan penelitian berupa coping strategi pemberdayaan ekonomi, serta relevan dan juga terakreditasi. Hasil analisis mengidentifikasikan ODHA dalam mengatasi permasalahan ekonomi yang dihadapinya dapat dibantu melalui strategi coping yang berfokus kepada masalah (problem focused copping) dengan melibatkan kolaborator dalam mengatasi permasalahan tersebut dengan melalui pemberdayaan ekonomi.